Optimum location for landfills landfill site selection using GIS technique: Al-Naja city as a case study. Issue 1 (1st January 2021) - L. Kareem, Sabreen; Al-Mamoori, Sohaib K.; Al-Maliki, Laheab A.; Al-Dulaimi, Mohammed Q.; Al-Ansari, Nadhir
Abstract: Solid waste is one of the leading environmental problems affecting human lives. Selecting a landfill where waste is disposed of is a complicated issue that related to many factors and regulations. In this study, the optimal sanitary landfill site for An-Najaf city was assessed using the GIS and weight criteria method. Eight appropriate criteria were selected, which are: urban area, rivers, roads, soil types, elevation, wind, slope, and archaeological, historical and religious sites. Moreover, the weighting of the criteria by using experts' opinion and previous similar literature. The "weighted overlay tool" is then applied to get a map of the significance index for selected landfill sites. Seven suitable sites with an area of 177, 762, 986 m 2 and form 0.62% from the total city area can accommodate the solid waste generated for a period, not less than ten years10 years.